Effect of hydroxyapatite reinforced high density polyethylene composites on mechanical and bioactivity properties - Husin, M.R. (Trans Tech Publications, 2011)
The biomaterial composites consisting of a polymer with a matrix addition of particulate bioactive phase that analogous to the bone microstructure had been extensively studied as a substitute for human's hard and soft tissues. In this work, HA reinforced HDPE composite (HDPE/HA) was made, with HA contents being up to 50 phr using single screw extruder nanomixer for the compounding process, and later followed by the injection moulding. These characteristics of the HDPE/HA composites were examined using various techniques including differential scanning calorimetry (DSC), scanning electron microscopy (SEM), tensile testing. Mechanical and thermal properties of the composite are differed when the amount of HA incorporated into the composite were varied. It is shown that HA particles were well dispersed and homogeneously distributed within the HDPE matrix. The elastic modulus and tensile strength were increased when the HA volume percentage increased from 10 phr to 50 phr with corresponding decreases in elongation at break. However no significant influence on thermal stability was found with increasing HA loadings. The enhancement of bioactivity has been proved while incorporation of HA into HDPE composite. SEM-EDX image showed the bulk formation of apatite layers on the composite surface with 30 wt% HA after 7 days immersed in simulated body fluid (SBF) solution. These results suggest the great potential of the composites for a range of temporary application in which bone bonding ability is a desired property.